Penerapan Model Pembelajaran Aktif dalam Mata Pelajaran PAI untuk Meningkatkan Motivasi dan Partisipasi Siswa - Putri, Alifa Fatria; Nawry, Najmi; Gusmaneli, Gusmaneli (YASIN, 2025)
The active learning model is a strategy that puts students at the center of the learning process so as to encourage their direct involvement in understanding the material. This study aims to analyze the application of the active learning model in Islamic Religious Education (PAI) subjects and its impact on student motivation and participation. The research method used is a qualitative approach with observation, interview, and document analysis techniques on teachers and high school students in the Padang area. The results show that the application of active learning models, such as group discussions, problem-based learning, and role-playing, is able to increase students' interest in learning and build critical and collaborative thinking skills. In addition, students are more enthusiastic in participating in learning because they feel they have a greater role in the learning process. Learning motivation increased along with active involvement in activities that encouraged the exploration of religious concepts in a more in-depth and applied way. Student participation has also increased significantly, shown by the activeness in asking questions, expressing opinions, and working together in groups. Thus, the active learning model in PAI not only improves conceptual understanding but also fosters an active and critical attitude in practicing Islamic teachings in daily life. Therefore, the application of the active learning model can be an effective alternative strategy in improving the quality of PAI learning in schools.